Intimate Partner Violence and Comorbid Mental Health Conditions Among Urban Male Patients - Rhodes, Karin V. (American Academy of Family Physicians, 2009)
PURPOSE We wanted to explore the associations between intimate partner violence (IPV) and comorbid health conditions, which have received little attention in male patients. METHODS Using a computer-based self-assessment health questionnaire, we screened sequential emergency department patients who were urban, male, and aged 18 to 55 years. We then examined associations between types of IPV disclosures, co-occurring mental health symptoms, and adverse health behaviors. RESULTS Of 1,669 men seeking nonurgent health care, 1,122 (67.2%) consented to be screened, and 1,026 (91%) completed the screening; 712 (63%) were in a relationship in the past year. Of these men, 261 (37%) disclosed IPV: 20% (n = 144) disclosed victimization only, 6% (n = 40) disclosed perpetration only, and 11% (n= 77) disclosed bidirectional IPV (defined as both victimization and perpetration in their relationships). Men disclosing both victimization and perpetration had the highest frequencies and levels of adverse mental health symptoms. Rates of smoking, alcohol abuse, and drug use were likewise higher in IPV-involved men. CONCLUSIONS A cumulative risk of poor mental health and adverse health behaviors was associated with IPV disclosures. Self-disclosure by men seeking acute health care provides the potential for developing tools to assess level of risk and to guide tailored interventions and referrals based on the sex of the patient.